Rasionalitas Pengambilan Keputusan Pemberi Sumbangan Kepada Pengemis di Kecamatan Cibinong - Jordan, Jansen Alson; Fauzi, Agus Machfud (Paradigma, 2024)
Limited job opportunities mean that individuals with low levels of education find it difficult to find work. Therefore, begging is a last resort for individuals who have no place in society. The distribution of beggars in Cibinong Subdistrict has increased from year to year. One of the factors for the outbreak of begging in Cibinong District is caused by donors who continue to give donations to beggars. The background of the donor shapes the morality of the individual in acting to give donations to beggars. Cibinong Sub-district has a prohibition for the community to give donations to beggars in Regional Regulation No. 7/2016 Article 57. The morality of the donor is influenced by the background of the donor who shapes the actions of each individual in the midst of applicable normative rules. The purpose of this study is to analyze the morality of donors who are influenced by religious, cultural, environmental and family backgrounds in Cibinong District. This research uses a qualitative approach with the perspective of Max Weber’s rationality theory. The data obtained in this study were obtained from observations and interviews conducted by researchers in depth. The results of this study indicate that individual morality influenced by religious background, family and environment in acting to give donations to beggars cannot be influenced by formal rules in Cibinong District. Lapangan pekerjaan yang terbatas menjadi penyebab individu dengan tingkat pendidikan rendah kesulitan dalam mencari pekerjaan. Oleh sebab itu, mengemis merupakan opsi terakhir bagi individu yang tidak mendapatkan tempat di dalam masyarakat. Penyebaran pengemis di Kecamatan Cibinong mengalami peningkatan dari tahun ke tahun. Salah satu faktor merebaknya pengemis di Kecamatan Cibinong disebabkan oleh pemberi sumbangan yang tetap memberikan sumbangan kepada pengemis. Latar belakang pemberi sumbangan membentuk moralitas pada diri individu dalam bertindak memberikan sumbangan kepada pengemis. Kecamatan Cibinong memiliki larangan bagi masyarakat untuk memberikan sumbangan kepada pengemis dalam Peraturan Daerah No 7 Tahun 2016 Pasal 57. Moralitas pemberi sumbangan dipengaruhi oleh latar belakang pemberi sumbangan yang membentuk tindakan masing-masing individu di tengah-tengah aturan normatif yang berlaku. Tujuan dari penelitian ini adalah untuk menganalisis moralitas pemberi sumbangan yang dipengaruhi oleh latar belakang agama, budaya, lingkungan dan keluarga di Kecamatan Cibinong. Penelitian ini menggunakan pendekatan kualitatif dengan perspektif teori rasionalitas Max Weber. Data yang didapat dalam penelitian ini diperoleh dari hasil observasi dan wawancara yang dilakukan peneliti secara mendalam. Hasil dari penelitian ini menunjukkan bahwa moralitas individu yang dipengaruhi latar belakang agama, keluarga dan lingkungan dalam bertindak memberikan sumbangan kepada pengemis tidak dapat dipengaruhi oleh aturan formal yang ada di Kecamatan Cibinong. Keywords: Rationality, donor, morality, formal rules